Belief in divine moral authority: Validation of a shortened scale with implications for social attitudes and moral cognition. (May 2016) - Simpson, Ain; Piazza, Jared; Rios, Kimberly
Abstract: Religion and morality have been deeply interwoven throughout human history. Although much research has investigated the role of religiosity (e.g., belief in God, prayer, religious attendance) in shaping moral concerns, only recently has research in psychology begun to delve deeper into the meta-ethical beliefs theists hold about the spiritual foundations of morality. The present research builds on moral–philosophical discourse on Divine Command Theory and recent work by Piazza and Landy (2013), who developed the 20-item Morality Founded on Divine Authority (MFDA) scale to measure Divine Command beliefs. We sought primarily to reduce the MFDA scale to increase its pragmatic utility; Confirmatory Factor Analysis revealed an optimal 5-item scale. Across four studies, this scale yielded levels of construct, convergent, and incremental validity equivalent to those of the 20-item scale. Compared with several other measures of religiosity and conservative thinking, the short MFDA was the strongest predictor of anti-atheist prejudice among U.S. religious believers and Indian Hindus (Studies 1a–1b) and largely explained religiosity's relationship with attitudes toward science (Study 1a) and moral cognitive outcomes including deontological reasoning (Study 2a) and prohibitive morality (Study 2b). We conclude with discussion about the practical utility of this scale in ongoing research into religion and moral cognition. Highlights: A shortened, 5-item scale measuring belief in divine moral command is established. The scale shows good construct, convergent, and incremental validity. Divine Command beliefs best explain religious believers' attitudes toward atheists. Also best explain believers' propensity toward deontological/prohibitive morality This scale should be important in ongoing research into religious/moral psychology.